LOCAL POLITICAL PARTIES IN ACEH IN 2017 REGIONAL ELECTION: Analysis of Political Identity and Islamization Issue - Syarif, Muhammad Rajiv (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The existence of local political parties in outline is a new alternative to the implementation of local democratic processes in Aceh are not specifically for Islamization issues. In the political record, the process of electing leaders in Aceh Province has been noted for three times (2006, 2012 and 2017). Aceh continues to move dynamically with political activities that are often rarely predictable or new conflicts that are sometimes expected to occur during democratic parties. This paper examines factors of voter's behavior and political identity in Aceh after the signing peace agreement in 2005 as well as analyzes the regional elections in 2017 and the Islamization issue within it. It will be explained that the behavior of voters in the Aceh regional election is very crucial. The election runs successfully by playing the identity of the political party in the Islamic shari'a area bringing issues in local implementation's policy. Finally, the crisis of trust that has been happening to national political parties has become one of the benchmarks for people to participate in the implementation of local democracy through the emergence of local political parties in Aceh.